Penentuan Validitas Modul Ikatan Kimia Berbasis Inkuiri Terbimbing - Suci Ulan Sari; Iryani Iryani (Edukimia, 2019)
This research aims to produce a guided-inquiry based module on Chemical Bonding, also to categorize validity of the module. It is a Research and Development which is used Plomp model which consists of three stages, preliminary research, prototyping stage and assessment phase. The instrument used for this research is questionnaire for validation. Was validated by 5 people, 3 lecturers of Chemistry Department FMIPA UNP and 2 chemistry teachers of SMA Pertiwi 1 Padang. The analysis result of validity sheet showed the average Kappa moment (k) was 0.86. The module that has been  produced is very valid to be used.